Progesterone receptor membrane component 1 and 2 regulate granulosa cell mitosis and survival through a NFΚB-dependent mechanism†. Issue 6 (16th March 2019) - Peluso, John J; Pru, Cindy A; Liu, Xiufang; Kelp, Nicole C; Pru, James K
Abstract: Progesterone receptor membrane component 1 (PGRMC1) interacts with PGRMC2, and disrupting this interaction in spontaneously immortalized granulosa cells (SIGCS) leads to an inappropriate entry into the cell cycle, mitotic arrest, and ultimately cell death. The present study revealed that PGRMC1 and PGRMC2 localize to the cytoplasm of murine granulosa cells of nonatretric follicles with their staining intensity being somewhat diminished in granulosa cells of atretic follicles. Compared to controls ( Pgrmc1 fl/fl ), the rate at which granulosa cells entered the cell cycle increased in nonatretic and atretic follicles of mice in which Pgrmc1 was conditionally deleted ( Pgrmc1 d/d ) from granulosa cells. This increased rate of entry into the cell cycle was associated with a ≥ 2-fold increase in follicular atresia and the nuclear localization of nuclear factor-kappa-B transcription factor P65; (NFΚ B/p65, or RELA). GTPase activating protein binding protein 2 (G3BP2) binds NFΚ B/p65 through an interaction with NFΚ B inhibitor alpha (IκBα), thereby maintaining NFΚ B/p65's cytoplasmic localization and restricting its transcriptional activity. Since PGRMC1 and PGRMC2 bind G3BP2, studies were designed to assess the functional relationship between PGRMC1, PGRMC2, and NFΚ B/p65 in SIGCs. In these studies, disrupting the interaction between PGRMC1 and PGRMC2 increased the nuclear localization of NFΚ B/p65, and depleting PGRMC1, PGRMC2, or G3BP2 increased NFΚ B transcriptional activity and the progression into the cell cycle. Taken together, these studies suggest that PGRMC1 and 2 regulate granulosa cell cycle entry in follicles by precisely controlling the localization and thereby the transcriptional activity of NFΚ B/p65. Abstract : PGRMC1 and 2 regulates granulosa cell mitosis.